An Early Sensitive Period Induces Long-Lasting Plasticity in the Honeybee Nervous System - Grosso, Juan P.; Barneto, Jesica A.; Velarde, Rodrigo A.; Pagano, Eduardo A.; Zavala, Jorge A.; Farina, Walter M. (Frontiers in Behavioral Neuroscience, 2018)
The effect of early experiences on the brain during a sensitive period exerts a long-lasting influence on the mature individual. Despite behavioral and neural plasticity caused by early experiences having been reported in the honeybee Apis mellifera, the presence of a sensitive period in which associative experiences lead to pronounced modifications in the adult nervous system is still unclear. Laboratory-reared bees were fed with scented food within specific temporal windows and were assessed for memory retention, in the regulation of gene expression related to the synaptic formation and in the olfactory perception of their antennae at 17 days of age. Bees were able to retain a food-odor association acquired 5-8 days after emergence, but not before, and showed better retention than those exposed to an odor at 9–12 days. In the brain, the odor-rewarded experiences that occurred at 5-8 days of age boosted the expression levels of the cell adhesion proteins Nrx1 and Nlg2 involved in synaptic strength. At the antennae, the experiences increased the electrical response to a novel odor but not to the one experienced. Therefore, a sensitive period that induces long-lasting behavioral, functional and structural changes is found in adult honeybees.